PENGARUH INTERAKSI SOSIAL TERHADAP MOTIVASI BELAJAR PESERTA DIDIK KELAS IV SEKOLAH DASAR - Deliani, Ni Wayan; Sofia, Ari; Izzatika, Amrina; Erni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The primary concern of this study is the low learning motivation among fourth-grade elementary school students. This research aims to determine the effect of social interaction on students’ learning motivation. This study employed a quantitative research method using an ex post facto approach. The population consisted of 189 students, with a sample of 129 students selected through proportionate stratified random sampling. Data were collected using a Likert-scale questionnaire that had been tested for validity and reliability, supported by observation and questionnaires. Data analysis was conducted using simple linear regression. The results showed that social interaction has a significant effect on the learning motivation of fourth-grade elementary school students.